MANAJEMEN PEMBINAAN OLAHRAGA BOLA VOLI PADA SISWA SMP N 1 MUARO JAMBI - Muhammad Raihan Apriwando; Palmizal; Yonifia Anjanika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the management of volleyball coaching for students at SMP Negeri 1 Muaro Jambi. The research employed a quantitative descriptive survey method. The population consisted of all students participating in the volleyball extracurricular program, totaling 15 students. Since the population was relatively small, a total sampling technique was applied. Data were collected using a questionnaire based on five management indicators: planning, organizing, coordinating, controlling, and evaluating. The data were analyzed using descriptive percentage analysis. The results showed that the overall management of volleyball coaching was categorized as high, with an average percentage of 72%. The planning indicator obtained 69%, organizing 73%, coordinating 70%, controlling 75%, and evaluating 74%, all of which were classified in the high category. These findings indicate that the implementation of volleyball coaching management at SMP Negeri 1 Muaro Jambi has been carried out effectively. However, improvements are still needed, particularly in planning, program evaluation, and the optimization of facilities and infrastructure to further enhance students' athletic achievements.